The numerical sense and its relationship to the mathematical achievement of the second grade intermediate students - Ahmed, Hiba Thamer (Thi Qar Arts Journal, 2021)
The current research aims to identify the correlation between the numerical sense and the mathematical achievement of mathematics for the second grade students in the middle school. In order to achieve this goal, the researcher adopted a scale (Karma, 1999) to measure the numerical sense, and the researcher also built an achievement test for mathematics, and after determining the research community represented by second-grade students in the middle school in the six districts in Baghdad governorate, the researcher pulled a stratified random sample from the community. (200) male and female students were estimated, and the research tools were applied to them. After applying the tools and collecting data, the data were analyzed by the Statistical Package for Social Sciences (SPSS) and the results were as follows: 1- There is a low level of numerical sense among middle school students 2- There is a low level of mathematical achievement in mathematics among second-grade students in average 3- There is a statistically significant relationship between numerical sense and mathematical achievement among middle school students The research reached a set of conclusions, recommendations and suggestions